Polymorphism in the tumor necrosis factor alpha promoter region and its influence on colorectal cancer predisposition risk in Malaysian population - Mohd Aminudin, Mustapha; Siti Nurfatimah, Mohd Shahpudin; Ahmad Aizat, Abdul Aziz; Bhavaraju, Venkata Muralikrishna; Naik, Venkatesh R; Zaidi, Zakaria; Ahmad Shanwani, Mohd Sidek; Mohammad Radzi, Abu Hasan; Ankathil, Ravindran (Japan International Cultural Exchange Foundation (JICEF), 2011)
objective:A case control study was designed to investigate the TNF-a -308 G>A polymorphism allele frequencies and to determine the influence of the polymorphic genotype on sporadic CRC susceptibility risk in Malaysia population. Material and methods: Peripheral blood samples of 164 normal controls and 161 clinically and histopathhologically confirm CRC patients were genotyped for TNF-a -308 G>A polymorphism employing allele specific PCR. The relative associations of various genotypes with CRC susceptibility risk was determined by calculating Odd ratios. Corresponding Chi-square tests on CRC patients and controls were carried out and 95% confidence interval (95% CI) were determined using fisher exact tests. Results: On comparing the frequencies of genotypes of patients and controls, the homozygous variant AA was significabtly higher in CRC patients (p=0.030) compared to controls. On investigating the association of the polymorphic genotypes with CRC susceptibility risk, the homozygous variant TNF-a -308AA showed significantly increased risk with OR 2.5842. Conclusion: Our results suggest that, polymorphic genotype of inflammation response gene TNF-a is significantly associated with CRC susceptibility risk and colud be considered as a high risk variant for CRC predisposition.